Polypropylene Nanofibers : Melt Electrospinning Versus Meltblowing - Nayak, Rajkishore (Engineering Materials,, 2017)
This book provides a comparison between melt electrospinning and meltblowing as techniques for the production of polypropylene nanofibers. The author compares the morphological, structural, chemical and mechanical characteristics of the different produced fibers. Moreover, the degree of thermal degradation of the different fibers is also analyzed. The book is useful to chemists and material scientists working on the synthesis of nanofibers by melt processes, showing the limitations of each technique for nanofiber fabrication.